Gluconic Acid Production from Potato Peel Wastes by Oxidation Using Silver(I) Ion - Mariappan, Sagevindren; Shrivastava, Preeti (International Journal of Engineering and Technology, 2018)
Gluconic acid (GA) is a non-corrosive acid used in textile, food additives and pharmaceutical skin care products. Many synthetic approaches were proved costly to produce GA in bulk. Potato peel as domestic waste is rich in nutritional value as they could also be used as fertilizer for plantations. However, improper disposable of these waste could lead to serious environmental problems due to insufficient supply of oxygen leading to an anaerobic condition for the unwanted growth of harmful microorganisms. This bacterial pollution might lead to foul smell and contagious air pollution. An attempt was made by using this potato peel waste to produce GA chemically in normal experimental laboratory condition with high yields. In the process, it was also made to estimate the precious silver metal produced. In present study, potato peel was used to convert the starch in peel to GA and metal silver by oxidation using silver ions. Potato peel wastes were hydrolyzed in acidic medium, where the starch and cellulose in peel were converted into glucose. This glucose was converted into GA using ammonical solution of silver nitrate solution. GA was separated using water as a solvent. The yield of GA was quantified by physicochemical and spectrophotometric methods. The GA is quantified by titration and the yield was found as 68 Â± 5% and the amount of silver metal powder was obtained 0.3Â±0.05 % per kilogram of potato peel waste. This process was simple, precise, accurate, environmental friendly, economical and meet the sustained development goals (SDG).Â Â